Особливості аналізу необоротних активів на прикладі підприємства ПАТ «Харківська бісквітна фабрика» - Савченко, Алла Миколаївна; Олянецька, Марина Сергіївна (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2019)
Від забезпеченості підприємства необоротними активами та ефективності їх використання багато в чому залежить його господарська діяльність та фінансовий стан. З огляду на це виникає необхідність у формуванні методичних засад аналізу необоротних активів підприємства, які можуть стати логічним доповненням методики проведення аналізу динаміки та структури необоротних активів. У статті висвітлено загальну характеристику необоротних активів підприємства та визначено поняття необоротних активів згідно з ПСБО. Проведено горизонтальний та вертикальний аналіз необоротних активів на прикладі ПАТ «ХАРКІВСЬКА БІСКВІТНА ФАБРИКА» та наведено існуючі методики аналізу. Визначені основні аналітичні показники та порядок їх розрахунку. Розраховано основні показники, які характеризують кількісний та якісний стан необоротних активів.

The security of the enterprise with fixed assets and the efficiency of their use largely depends on the economic activity and financial condition of the enterprise. In view of this, there is a need for the formation of methodological bases for the analysis of fixed assets of the enterprise, which can be a logical complement to the methodology of analysis of the dynamics and structure of fixed assets. The article describes the general characteristics of non-current assets of the enterprise and provides their general classification according to PSO. Horizontal and vertical analysis of non-current assets on the example of PJSC "Kharkiv Biscuit Factory" is carried out and the existing methods of analysis are given. The main analytical indicators and the order of their calculation are determined. The basic indicators characterizing the quantitative and qualitative state of non-current assets are calculated. Due to the introduction of mandatory analysis of non-current assets at the enterprise, it will be possible to promptly determine the technical condition of fixed assets, the use of production facilities, the impact of economic operations with non-current assets on the financial condition and financial results of the enterprise. The study confirms that the analysis of non-current assets makes it possible to expand output and sales without additional involvement of resources or to determine the need for restoration or expansion of production capacity Non-current assets are one of the most important objects of economic sciences, in particular accounting. Non-current assets in current conditions farms play a decisive role as they are constitute a significant part of the property of any entity management. In the process of managing a production enterprise, performing works or providing services, and for management purposes use non-current assets that make up a large part of them capital. This is especially true of manufacturing enterprises where the share of fixed assets in the general capital structure may reach more than half, so an objective analysis of fixed assets is important to ensure effective management of economic processes activities.
Keywords: аналіз; необоротні активи; основні засоби; інвестиції; фінансова звітність; analysis; non-current assets; fixed assets; investments; financial statements